Dampak Penerapan Konsep Pariwisata Berkelanjutan Terhadap Masyarakat di Kampung Tobati Enggros Kota Jayapura - Darmina Wandik; Lazarus Ramandei; Juliani Wairata (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study analyzes the impact of sustainable tourism concept implementation on the community of Tobati-Enggros Village, Jayapura City. Using qualitative descriptive methods with in-depth interviews, participatory observation, and document analysis involving 35 informants, this research evaluates three pillars of sustainability: economic, socio-cultural, and environmental aspects. The findings show that sustainable tourism implementation achieves a moderate effectiveness score of 2.7. Economically, tourism creates new employment opportunities and increases community income by 25%-400%, but benefits distribution remains unequal with 70% of profits controlled by 30% of residents. Socio-culturally, tourism helps preserve the unique